Biochar As Plant Growth Promoter: Better Off Alone or Mixed with Organic Amendments? - Bonanomi, Giuliano; Ippolito, Francesca; Cesarano, Gaspare; Nanni, Bruno; Lombardi, Nadia; Rita, Angelo; Saracino, Antonio; Scala, Felice (Frontiers in Plant Science, 2017)
Biochar is nowadays largely used as a soil amendment and is commercialized worldwide. However, in temperate agro-ecosystems the beneficial effect of biochar on crop productivity is limited, with several studies reporting negative crop responses. In this work, we studied the effect of 10 biochar and 9 not pyrogenic organic amendments (NPOA), using pure and in all possible combinations on lettuce growth (Lactuca sativa). Organic materials were characterized by 13C-CPMAS NMR spectroscopy and elemental analysis (pH, EC, C, N, C/N and H/C ratios). Pure biochars and NPOAs have variable effects, ranging from inhibition to strong stimulation on lettuce growth. For NPOAs, major inhibitory effects were found with N poor materials characterized by high C/N and H/C ratio. Among pure biochars, instead, those having a low H/C ratio seem to be the best for promoting plant growth. When biochars and organic amendments were mixed, non-additive interactions, either synergistic or antagonistic, were prevalent. However, the mixture effect on plant growth was mainly dependent on the chemical quality of NPOAs, while biochar chemistry played a secondary role. Synergisms were prevalent when N rich and lignin poor materials were mixed with biochar. On the contrary, antagonistic interactions occurred when leaf litter or woody materials were mixed with biochar. Further research is needed to identify the mechanisms behind the observed non-additive effects and to develop biochar-organic amendment combinations that maximize plant productivity in different agricultural systems.